Charles S : Peirce and the Linguistic Sign. (Foundations of semiotics ;, 1985)
This monograph is about the semiotics of lexical signs, and is of particular interest for historical linguists, in particular those interested in etymology. Specialists in linguistic change have long noticed that certain classes of words seem to be in part exempt from regular patterns of sound change, or perhaps more likely to undergo unusual analogical shifts. The problem is far worse for the etymologist, since the lexicon of every language contains some hundreds of semiotically problematic vocables which must, if the etymological dictionaries are ever to be completed, be explained somehow. Always been struck by the sheer capriciousness of etymologies in which some sort of unusual form-meaning relations are involved, the author, with the help of C.S. Peirce, provides answers to crucial questions in his search to make sense of those capricious etymologies.